A Two-Day Acceptance and Commitment Therapy (ACT) Workshop Increases Presence and Work Functioning in Healthcare Workers - Gaupp, Rainer; Walter, Marc; Bader, Klaus; Benoy, Charles; Lang, Undine E. (Frontiers in Psychiatry, 2020)
Background: In this controlled naturalistic study performed in healthcare workers we examined the effect of a two-day acceptance commitment therapy (ACT) workshop on work presence and productivity, i.e. the influence the workshop had on treatment efficacy in a routine hospital care setting. Aim: To examine the influence of ACT on productivity and absentism in healthcare workers. Method: Study participants were all healthcare workers (nurses, medical doctors, physiotherapists and art therapists) of four inpatient wards for depression. Half of the healthcare workers attended the workshop. Measures were evaluated 3 months after the intervention in the study participants and the patients treated by them in the same time period. Results: A significantly higher treatment efficacy (as measured with HoNOS change in the patients treated by the participants) has been observed in the healthcare workers who attended the ACT workshop when compared to the control group who did not attend the workshop. Moreover, the work presence of the participants of the ACT workshop was increased when compared with the time period before the intervention and with the presence of the control group. A cost analysis showed that ACT workshops lead to a significant return of investment for the employer as the costs for the workshop were ten times compensated by the increase of work presence in participants of the workshop. Conclusion: These findings provide support that ACT interventions motivate healthcare workers to work and increase their patients treatment quality. To our knowledge this is the first study showing an ACT workshop in healthcare workers can influence HoNOS outcome in the treated patients.